Rosiglitazone Did Not Induce Acute Kidney Injury in Normocholesterolemic Rats Despite Reduction in Glomerular Filtration Rate - Cristiano Dias; Rildo A. Volpini; Claudia M.B. Helou (Karger Publishers, 2014)
Background/Aims: Rosiglitazone (RGL) has been used to ameliorate lipids homeostasis and also to treat inflammatory diseases. However, RGL may reduce renal blood flow and glomerular filtration rate (GFR) predisposing to acute kidney injury (AKI). We investigated whether the treatment with RGL induces AKI in normocholesterolemic (NC) and hypercholesterolemic (HC) rats. Methods: We measured GFR by inulin clearance technique and we quantified urinary neutrophil gelatinase-associated lipocalin (uNGAL) in all groups at baseline and during Ang II-stimulated vasoconstriction. Moreover, we evaluated the presence of renal damaged by histologic examination. Results: At baseline, NC and HC had normal and similar GFR. RGL treatment reduced GFR only in NC+RGL. Unexpectedly, HC+RGL showed high levels of uNGAL although GFR was at normal range. During Ang II-stimulated vasoconstriction, all groups showed reduction in GFR to the same range and we found high levels of uNGAL and high score of renal damage in HC and HC+RGL. Conclusion: RGL acts distinctly in normocholesterolemia and in hypercholesterolemia. Reduction in GFR provoked by RGL treatment did not allow the diagnosis of AKI in NC even in the presence of ANG II-stimulated vasoconstriction. However, AKI was diagnosed in HC+RGL at baseline although GFR was within normal range.